Short range order of glassy KSb5S8 by diffraction, EXAFS, vibrational spectroscopy and DFT calculations - Jóvári, P.; Chrissanthopoulos, A.; Andrikopoulos, K.S.; Pethes, I.; Kaban, I.; Kohara, S.; Beuneu, B.; Yannopoulos, S.N. (Journal of Non-Crystalline Solids, 2023)
We report on a detailed experimental and simulation study of the short- and medium-range order of a potential phase change material – glassy KSb5S8. On the experimental side, diffraction techniques and EXAFS have been employed to record accurate structural data. Structural models have been generated by fitting multiple datasets simultaneously with the reverse Monte Carlo simulation technique. In addition, density functional theory was employed to study the structure and vibrational modes of selected clusters, representative of the glass structure. Unconstrained RMC simulation runs revealed that the average Sb-S coordination number is 3.18 ± 0.2, thus Sb is mostly threefold coordinated in the glassy state. The fraction of edge and corner sharing SbSn polyhedra and distribution of bridging S atoms (Qn distribution) have also been obtained. Distribution of bridging S atoms around Sb is similar in the crystalline and glassy states. DFT calculations assisted in the identification of a Raman mode at ∼468 cm−1, assigned to hypervalent bonding (quasi-tetrahedral units) in the glass structure.